Analisis Persepsi Wajib Pajak UMKM Terhadap Peraturan Pemerintah No. 23 Tahun 2018 - Esi Rahmadini; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze the understanding and perception of SMEs Taxpayers towards Government Regulation Number 23 of 2018 in Padang. This research is a qualitative method with a phenomenological approach. Data was collected through interviews, observation and documentation. Interviews were conducted on four types of SMEs Padang namely culinary, trade, services and handicraft industries with ten informants who fulfill their tax obligations according to Government Regulation Number 23 of 2018. The research process was carried out interactively and obtained meaning that was not measurable by statistical data and aims to explore various information in more depth and make it possible to get things implied. Data analysis is inductive and qualitative research. This study found that the level of understanding of taxpayers was not so good because most taxpayers only understand Government Regulation Number 23 of 2018 limited to a reduction in tax rate to 0.5%. The results also found that taxpayers welcomed the reduction in tax rate, the self assessment system was considered ineffective, the deadline and bookkeeping obligations were considered confusing for taxpayers. Government outreach is the main determinant of the implementation of Government Regulation Number 23 of 2018